Penerapan Konsep Eco-Lingkungan di Sekolah Dasar Alam Qur’an Bintang Madani, Bandar Lampung: Implementing the Eco-Environment Concept at the Bintang Madani Qur’an Nature Elementary School, Bandar Lampung - Ilham Fatoni; Muzekki Muzekki; Indah Nur Bella Sari; Ikhsan Mustofa; Ali Murtadho; Baharudin Baharudin (Al-Musannif, 2024)
Environmental issues are becoming more complex, yet integrating environmental education into the school curriculum remains challenging. Many schools struggle to implement sustainable practices due to limited resources and a lack of awareness among stakeholders. This study analyzes the implementation of the eco-environment concept at Bintang Madani Qur'an Nature Elementary School, focusing on the integration of environmental programs in the curriculum and school activities, challenges faced, and the solutions applied. The study used a qualitative approach with a case study method. Data were collected through observations, interviews, and documentation. The results indicate that the school has implemented eco-environmental principles by engaging in greening initiatives, managing waste effectively, and utilizing environmentally friendly energy programs. The program's challenges include limited funds and facilities, resource constraints, limited understanding of the green school concept, and inconsistencies in program implementation. To address these challenges, the school, in cooperation with external institutions, provides training for teachers and students, involves the community in sustainability programs, and strengthens institutional management. This study has implications for the development of environmental education theory and practice based on local and religious values. It is the basis for formulating more contextual and applicable environmental education policies at the regional and national levels.